Waste Banks Management Information System Using K-Means Cluster Approach Based On Geographic Information System - Irfan Muhammad (EDP Sciences, 2021)
Natural disasters due to climate change can cause thousand tons of waste and the loss of human life, environmental damage and also economic losses each year. One of the ways to increase the effectiveness of waste management is by conducting waste banks activities as a community based environmental governance. Here, waste banks can be considered as a valuable economic commodity and savings. The supporting factor for the success of waste banks activity is through a technological instrument as a community based management which encourage the innovations for developing waste banks to be more effective and integrated. The method applied to the waste banks management system is a combination of the k- means cluster and the geographic information system (GIS) to identify groups of waste banks that have identical types of waste and also their distribution. The waste banks information system is able to provide information of the distribution of waste, waste production, the selling price of waste, and also groups of waste banks that have identical types of waste. The data used are 50 waste banks over a period of 8 months. The waste banks information system is able to perform classification in order to evaluate the distribution of waste.